HUBUNGAN KEPERCAYAAN NASABAH DAN PROMOSI DENGAN MINAT MENABUNG PADA PT. BANK BENGKULU KCP PADANG JAYA KABUPATEN BENGKULU UTARA - Suwarni Suwarni; Siti Aisyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The purpose of this study is to find out the correlation of customers’ trust with saving interest in at PT. Bank Bengkulu KCP Padang Jaya North Bengkulu Regency and to find out the relationship between the promotion with saving interest at PT. Bank Bengkulu KCP Padang Jaya of North Bengkulu Regency. The analytical method used was Spearman rank correlation and hypothesis testing. From the results of the Spearman rank correlation calculation between the customers’ trust with saving interest at PT. Bank Bengkulu KCP Padang Jaya of North Bengkulu Regency, it is known that the value of rho count is 0.562, which means the correlation between customers’ trust and saving interest at PT. Bank Bengkulu KCP Padang Jaya of North Bengkulu Regency is moderate, because the correlation value is in the coefficient interval of 0.400 - 0.599, then the correlation between promotions and customers saving interest with the value of rho count is 0.608, which means strong correlation, because the correlation value is in the coefficient interval of 0.600 - 0.799. From the hypothesis testing between the customers’ trust and saving interest with the value of t count is greater than t table (5,131> 1,672) meaning that the hypothesis proposed in this study proved that customer trust has a significant correlation with the customers saving interest at PT. Bank Bengkulu KCP Padang Jaya North Bengkulu Regency. Then the hypothesis testing between promotions with the customers saving interest with the value of tcount is greater than ttable (5,782> 1,672) meaning that the hypothesis proposed in this study proved that the promotion has a significant correlation with the customers saving interest at PT. Bank Bengkulu KCP Padang Jaya of North Bengkulu Regency.